Trust-based mechanisms for secure communication in cognitive radio networks - Parvin, Sazia (Curtin University, 2013)
Cognitive radio (CR) technology was introduced to solve the problem of spectrum scarcity to support the growth of wireless communication. However, the inherent properties of CR technology make such networks more vulnerable to attacks. This thesis is an effort to develop a trust-based framework to ensure secure communication in CRN by authenticating trustworthy nodes to share spectrum securely and increasing system's availability and reliability by selecting the trustworthy key nodes in CRNs.